Self-powered wireless sensor system for water monitoring based on low-frequency electromagnetic-pendulum energy harvester - Li, Mingxue; Zhang, Yufeng; Li, Kexin; Zhang, Yiwen; Xu, Kaixuan; Liu, Xiaoqiang; Zhong, Shaoxuan; Cao, Jiamu (Energy (Oxford), 2022)
Using wireless sensor network technology to monitor water quality has the advantages of high real-time and low cost, which is very helpful for preventing water pollution. However, traditional wireless sensor nodes adopt batteries as power source which has limited capacity. The effective way to solve power issues for wireless sensor nodes is directly obtaining environmental energy and converting it to electricity. In this work, a water-wave energy self-powered wireless water quality sensor node system is designed. A small water wave vibration energy harvester is designed and used as the power supply device for the self-powered system. The energy harvester has a low operating frequency of 1.5 Hz and the RMS power reaches 14.76 mW. In addition, the power management system and low power wireless sensor system are designed and implemented in conjunction with the energy harvester. The power management system and the low-power water quality wireless sensor with total dissolved solids (TDS) and temperature sensing function are implement for the energy harvester. These parts are packaged in a small float to form the self-powered system which reports data wirelessly when driven by water wave. The self-powered system has a good application prospect in the field of long-term unattended water environmental monitoring. •Low-frequency vibration energy harvester is realized with high power density.•Hardware and software optimization are used to reduce power consumption of load.•Efficient energy management system is designed for self-powered wireless sensing.•Full work cycle can be realized under low frequency and wideband water wave drive.